The Role of Legal Politics in the Recovery of State Financial Losses Due to Corruption - Hamdan, Riko; Nuraya, Adha; Syam, Fauzi (Fakultas Syariah INSURI Ponorogo, 2024)
Corruption crimes have caused very large losses to the state and can have an impact on the emergence of various crises in various fields such as social life, nationhood, and statehood. Therefore, a legal enforcement method is needed through the establishment of a special body that has broad, independent, and free authority from any power in efforts to eradicate corruption crimes that are carried out maximally, intensively, effectively, professionally, and continuously. This paper uses a normative juridical research method through an approach based on basic legal materials by examining theories, concepts, legal principles, and regulations. Research using a normative juridical method is legal research conducted by examining literature or secondary data as a basis for research by tracing regulations and literature related to the issues being studied. To solve the legal problems that have been formulated and get their answers, this research uses four problem-solving approach models, namely the statutory approach, comparative approach, historical approach, and conceptual approach. The results of this study are various changes and reviews of anti-corruption laws that are legal policies applied by Indonesia as efforts towards legal reform for the better. Because corruption has harmed state finances, efforts to recover state financial losses are carried out through criminal, civil, and administrative channels.